PENINGKATAN SIKAP PERCAYA DIRI MELALUI STRATEGI PEMBELAJARAN ATONG BERBATU MEDIA POWTOON DI SEKOLAH DASAR - Aji Heru Muslim (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Purwokerto, 2020)
Abstract. This study aimed to improve the students confidence through ATONG learning strategies with Powtoon-based video as the media. The subjects were the students of class V of Primary School that consisted of 26 students, 13 female and 13 male students. It was a Classroom Action Research that conducted in 2 cycles. Each cycle consisted of one meeting with the allocation time of 6x35 minutes for each meeting. The procedure of each cycle consisted of planning, acting, observing, and reflecting. The data on the results of self-confidence were obtained by using questionnaires, observations, and documents. In cycle 1, based on the questionnaire, the students self-confidence in the learning process obtained 74.23 with good criteria and based on the observation, the students self-confidence in the learning process obtained 3.67 with good criteria. In cycle II, based on the questionnaire, it increased to 86 with very criteria, and based on the observation sheet, it increased to 3,992 with good criteria. Therefore, it can be concluded that ATONG learning strategy with the Powtoon-based video as the media is able to improve the students self-confidence in class V of Primary School. Abstrak. Penelitian ini bertujuan untuk meningkatkan sikap percaya diri siswa menggunakan strategi pembelajaran ATONG dengan bantuan media video berbasis powtoon. Subyek penelitian adalah siswa kelas V Sekolah Dasar dengan jumlah 26 yang terdiri dari 13 perempuan dan 13 laki-laki. Penelitian ini adalah Penelitian Tindakan Kelas dalam 2 siklus. Setiap siklus terdiri dari 1 pertemuan dengan masing-masing pertemuan terdiri dari 6x35 menit. Prosedur pelaksanaan setiap siklus terdiri dari perencanaan, pelaksanaan, tindakan, observasi dan refleksi. Data hasil sikap percaya diri siswa diperoleh dari angket, observasi dan dokumen. Pada siklus 1 hasil angket yang diperoleh siswa dalam proses pembelajaran yaitu 74,23 dengan kriteria baik dan hasil dari lembar observasi sikap percaya diri yang diperoleh siswa dalam proses pembelajaran yaitu 3,67 dengan kriteria baik, pada siklus II mengalami peningkatan menjadi 86 dengan kriteria baik sekali dan hasil dari lembar observasi sikap percaya diri mengalami peningkatan 3,99 dengan kriteria baik. Dengan demikian dapat disimpulkan bahwa strategi pembelajaran ATONG dengan bantuan media video berbasis powtoon dapat meningkatkan sikap percaya diri siswa kelas V Sekolah Dasar.